Drivers Affecting The Gold Price - Bhuptani, Vinit (2009)
Gold is tagged as a king of metals. From ornamentation to financial purpose, the yellow metal has satisfied both kinds of needs. The price of gold has reached a new high in the recent past. Various political and financial reasons have a strong influence on the price of gold. However, there are few drivers that have tremendous impact on the movement of the gold price. The period of their (drivers) occurrence and the impact on the gold price during that time is discussed in detail. The relationships of the selected drivers with the gold price are discussed on the basis of the past data. These relationships are further justified by discussing the actual happenings in the past and how did gold price faired during this time. A time series model is used to analyse the impact of these drivers on gold price on the basis of the past data.